Bed-Based Ballistocardiography System Using Flexible RFID Sensors for Noninvasive Single- and Dual-Subject Vital Signs Monitoring - Escobedo, Pablo; Pousibet-Garrido, Antonio; Lopez-Ruiz, Nuria; Carvajal, Miguel A.; Palma, Alberto J.; Martinez-Olmos, Antonio (IEEE transactions on instrumentation and measurement, 2024)
This work presents an innovative approach employing passive radio frequency identification (RFID) technology to develop a comprehensive ballistocardiography (BCG) system for contactless and noninvasive vital sign monitoring of individuals on a mattress. The method relies on wireless energy transfer through inductive coupling at 13.56 MHz between an active powering board and a passive, flexible sensing board with dimensions of 12.6×4.7 cm2. Both boards face each other at a separation distance of 3 cm. The system demonstrates remarkable sensitivity to mattress vibrations resulting from bodily movements, rendering it proficient in generating complete BCG signals capable of discerning heart rate (HR), breathing rate (BR), and activity. Practical trials with six healthy subjects validated the feasibility and efficacy of the system, showing an average absolute error of 1.8 beats/min for HR and 0.6 breaths/min for BR. Unlike conventional BCG systems, the sensing module seamlessly integrates into the mattress side. This is leveraged to enable the simultaneous monitoring of two subjects on a queen-size mattress, taking advantage of the local sensitivity of the sensing mechanism. Extracted BCG values can be wirelessly transmitted to the user's smartphone through near-field communication (NFC) and to a cloud service used for storage, distribution, and categorization of subject data. This work establishes a foundation for future extensive studies and applications, as the obtained BCG signals could provide health-related insights, such as detecting heart diseases, respiratory problems, or evaluating sleep quality.